Allelopathic effects of Dioscorea hispida Dennst. (Dioscoreaceae) tuber from Terengganu, Peninsular Malaysia - Nornasuha, Yusoff; Zanariah, Mat Isa; Nashriyah, Mat; Wan Izyani Adilah, Wan Mohamad (2012)
The allelopathic effects of water extract and methanol crude extract from Dioscorea hispida Dennst. (Ubi gadung) tuber was tested on the seeds of selected crops in petri dishes. Experiments were conducted to determine the effects of water extract and methanol crude extract on the germination, radicle length and fresh weight of bioassay test species; namely maize (Zea mays), mustard (Brassica sp.), cucumber (Cucumis sp.), spinach (Amaranthus sp.) and radish (Raphanus sp.). The results showed that the water extracts gave significant effects on germination rate and radicle length of these bioassay species. The water extract strongly inhibited the germination and radicle length of mustard (Brassica sp.) at 12.5 g/L and 50.0 g/L concentrations. Besides, the concentration of water extract at 25.0 g/L inhibited the germination and radicle length of Cucumis sp. However, the concentration at 12.5 g/L stimulated the germination and radicle length of maize (Zea mays). These results also showed that the methanol crude extracts gave significant effects on radicle length of bioassay species. It significantly inhibited the radicle length of all bioassay species; mustard (Brassica sp.), cucumber (Cucumis sp.), spinach (Amaranthus sp.) and radish (Raphanus sp.) at all concentrations.